2019
DOI: 10.1021/acs.inorgchem.8b03334
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Isomerism in [{MFe(CO)4}n]n (M = Cu, Ag, Au; n = 3, 4) Molecular Clusters Supported by Metallophilic Interactions

Abstract: Triangular clusters [{MFe­(CO)4}3]3– (M = Cu, 4; Ag, 5; Au, 6) were selectively obtained by heating Fe­(CO)4(MIMes)2 (M = Cu, 1; Ag, 2; Au, 3; IMes = C3N2H2(C6H2Me3)2). 1–3 were synthesized by reacting Na2[Fe­(CO)4]·2thf with 2 equiv of M­(IMes)­Cl. As previously described, the direct reactions of Na2[Fe­(CO)4]·2thf with one equivalent of M­(I) salts resulted in the triangular cluster [{CuFe­(CO)4}3]3– for Cu, whereas the square clusters [{MFe­(CO)4}4]4– were formed for Ag and Au. Thus, depending on the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 38 publications
7
38
0
Order By: Relevance
“…The NBO analysis revealed the weak interactions between adjacent silver atoms (10–15 kcal · mol –1 ). The distances in 2 are comparable to these observed in [Ag 2 (NO 3 ) 2 ‐{C 4 H 2 S(CONMe‐4‐C 5 H 4 N) 2 } 2 ], [Ag 2 (CF 3 CO 2 ) 2 {C 4 H 2 S(CONMe‐4‐C 5 H 4 N) 2 } 2 ] (intermolecular Ag ··· Ag = 3.48 Å) and are longer than these observed in [Ag 4 {Fe(CO) 4 } 4 ] 4– (3.036(1)–3.334(1) Å) . The arrangement around P2 and P4 atoms in 1 (∑P2 = 317.46(14)° and ∑P4 = 319.19(15)°) and P2, P4, P6 and P8 in 2 (∑P2 = 318.4(2)°, ∑P4 = 320.9(3)°, ∑P6 = 317.1(3)° and ∑P8 = 319.1(2)°) is clearly pyramidal.…”
Section: Resultssupporting
confidence: 68%
“…The NBO analysis revealed the weak interactions between adjacent silver atoms (10–15 kcal · mol –1 ). The distances in 2 are comparable to these observed in [Ag 2 (NO 3 ) 2 ‐{C 4 H 2 S(CONMe‐4‐C 5 H 4 N) 2 } 2 ], [Ag 2 (CF 3 CO 2 ) 2 {C 4 H 2 S(CONMe‐4‐C 5 H 4 N) 2 } 2 ] (intermolecular Ag ··· Ag = 3.48 Å) and are longer than these observed in [Ag 4 {Fe(CO) 4 } 4 ] 4– (3.036(1)–3.334(1) Å) . The arrangement around P2 and P4 atoms in 1 (∑P2 = 317.46(14)° and ∑P4 = 319.19(15)°) and P2, P4, P6 and P8 in 2 (∑P2 = 318.4(2)°, ∑P4 = 320.9(3)°, ∑P6 = 317.1(3)° and ∑P8 = 319.1(2)°) is clearly pyramidal.…”
Section: Resultssupporting
confidence: 68%
“…Crystal data of the new salts were included as Supporting Information and deposited within the Cambridge Crystallographic Datacenter for sake of completeness. All these salts contained the [Ag 3 Fe 3 (CO) 12 ] 3– ( 7 ), [Ag 4 Fe 4 (CO) 16 ] 4– ( 8 ), and [Ag 5 Fe 4 (CO) 16 ] 3– ( 9 ) cluster anions, that were already described in the literature (Figures S33–S35 in Supporting Information). Their formation suggested that the Ag–IMes bond was mainly broken during work‐up, leading to homoleptic Ag–Fe–CO clusters.…”
Section: Resultsmentioning
confidence: 94%
“…In particular, attempting the isolation of 3 , crystals of [NEt 4 ] 2 [Ag(IMes) 2 ][Ag 3 Fe 3 (CO) 12 ] · solv, [NEt 4 ] 2 [HIMes] 2 [Ag 4 Fe 4 (CO) 16 ], [NEt 4 ] 4 [Ag 4 Fe 4 (CO) 16 ] · 2CH 3 CN and [NEt 4 ] 3 [Ag 5 Fe 4 (CO) 16 ] were obtained. Crystal data of the new salts were included as Supporting Information and deposited within the Cambridge Crystallographic Datacenter for sake of completeness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations